Application of the leadership model in health services: a systematic review - Siti Aminah; Trias Mahmudiono (Journal of Public Health in Africa, 2023)
Introduction: Leadership is a process similar to management in many ways. Leadership involves influence, as does management. Leadership requires working with people who need management as well. Leadership is concerned with the effective attainment of goals, and so is management. Effective leadership of health professionals is very important to strengthen the quality and integration of health services and effective leadership also depends on the approach or leadership style adopted.